2003
DOI: 10.1063/1.1570951
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and application of plasma charge current in deep penetration laser welding

Abstract: Plasma charge current distribution during deep penetration CO2 laser welding was analyzed theoretically and experimentally. The laser-induced plasma above the workpiece surface expands up to the nozzle, driven by the particle concentration gradient, forming an electric potential between the workpiece and the nozzle due to the large difference between the diffusion velocities of the ions and the electrons. The plasma-induced current obtained by electrically connecting the nozzle and the workpiece can be increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…For instance, the inhomogeneous distribution of electron / ion density in the plasma cloud had been utilized to obtain signals characteristic for the welding process: In [22] the voltage drops between the work piece and the electrically insulated nozzle is taken as a sensor signal indicating various faults. A similar approach was presented in [23] where this potential was used to control the distance between nozzle and work piece. Basic studies such as, e.g.…”
Section: Laser Induced Plasma As Source For a Current In The Weld Poolmentioning
confidence: 94%
“…For instance, the inhomogeneous distribution of electron / ion density in the plasma cloud had been utilized to obtain signals characteristic for the welding process: In [22] the voltage drops between the work piece and the electrically insulated nozzle is taken as a sensor signal indicating various faults. A similar approach was presented in [23] where this potential was used to control the distance between nozzle and work piece. Basic studies such as, e.g.…”
Section: Laser Induced Plasma As Source For a Current In The Weld Poolmentioning
confidence: 94%
“…It can explain both magnitude and sign of the experimentally observed potential difference during laser welding. The sheath effect has been proposed as mechanism for the potential difference observed between the workpiece and the nozzle in [3], but neglecting the fact that two sheaths form, one at the hot end and one at the cold end. However, since the sheath effect alone cannot explain the sign of the current observed in [5], we conclude that both effects are important and should be taken into account when calculating currents induced by a plasma cloud forming above a locally heated metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Another process induced by the plasma is the generation of electrical voltages and currents since the plasma contains free electrical charges. Such currents have been observed between workpiece and gas nozzle [3] and it has been shown that applying a magnetic field can control the plasma. An explanation of the observed current between workpiece and nozzle has also been put forward on the basis of sheath theory [3], neglecting however the effect that sheaths will form at both the hot and the cold side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser-induced plasma above the workpiece surface diffuses towards the nozzle driven by the particle concentration gradient, so an electric potential is formed between the workpiece and the nozzle due to the large differences between the ion and electron diffusion velocities. Some experimental studies have measured the PCS signal variation with various welding conditions and the corresponding weld quality [18][19][20][21][22][23][24]. Li et al [19,20] described the mechanism of the PCS signal generation and developed an equation V p = 4.5kT e (where V p is the induced PCS voltage, k the Boltzmann constant and T the plasma temperature) to predict the voltage induced in the PCS.…”
Section: Introductionmentioning
confidence: 99%